Literatura utópica e seu pesadelo distópico: o protagonista dissidente em nineteen eighty-four - Azevedo, Taiana Teixeira (2017)
This work investigates literary utopias and dystopias; their definitions, similarities and distances as genre. Based on theoretical considerations regarding these two different ways of imagining totalitarian societies, with no space for individuality, we pursue to trace a continuum that comprehends the transformation of the utopian genre to the dystopian. After considerations about the genre, George Orwell's dystopian novel Nineteen eighty-four (published on 8 June 1949) is emphasized. The novel is a reference in the dystopic genre’s studies and characterizes its classical form, including its protagonist in his search for individuality in an extremely controlling space. This dissident character is an expressive feature of literary dystopias, for this reason, besides analyze aspects of the totalitarianism on Orwell’s novel, also, will be highlighted the path of the protagonist, Winston Smith, during his lonely resistance to the dystopian society.